Potential climate change impacts on surface water resources of Gomti River basin in India - ABEYSINGHA1, N. S.; SINGH, MAN; ISLAM, ADLUL; SEHGAL, V. K.; KHANNA, MANOJ; PATHAK, HIMANSHU (Journal of Soil and Water Conservation, 2021)
The impacts of climate change on surface water resources (SWRs) in Gomti River basin (India) were investigated by integrating a widely used hydrological model, Soil and Water Assessment Tool (SWAT) and MIROC (HiRes) GCM climate change projections. The SWAT model was calibrated and validated using monthly streamflow data of four spatially distributed gauging stations. Climate change scenarios were developed for A2, A1b and B1 emission scenarios for three future periods 2020s (2010–2039), 2050s (2040–2069) and 2080s (2070–2099). Mean annual rainfall were projected to increase by 10 to 18%, 15 to 47%, and 20 to 30% during the 2020s, 2050s and 2080s, respectively, and the associated SWRs of the basin in annual scale were also likely to increase by 7 to 29%, 17 to 35%, and 35 to 46% during the 2020s, 2050s and 2080s, respectively, compared to present day climate depending upon the emission scenarios. Simulation results also revealed greater changes in rainfall, and SWRs in the upstream sub-basin as compared to the downstream sub-basin.